PERAN INDONESIA DALAM MENINGKATKAN KERJA SAMA DI KAWASAN ASEAN - maharani, Deswita; Silvia Sinaga, Masdiana; Pangihutan Simangunsong , Raja; Alzazeera , Jihan; Suranta Sembiring, Imanuel; Tanjung, Flores (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze Indonesia's role in enhancing cooperation within the Association of Southeast Asian Nations (ASEAN). The study uses a qualitative approach with a literature study method through the analysis of various books, scientific journals, and relevant official documents. The results of the study indicate that Indonesia has a strategic position as one of the founding countries and the largest country in the Southeast Asian region. Indonesia plays an active role in strengthening regional political and security stability through various initiatives, such as the ASEAN Outlook on the Indo-Pacific and participation in defense forums and security cooperation mechanisms. In addition, Indonesia also encourages regional economic integration by strengthening the ASEAN Economic Community and contributing to maintaining the stability of regional economic growth. In the fields of humanity and international law, Indonesia also strengthens regional solidarity through disaster management cooperation and maritime diplomacy in line with the recognition of the concept of an archipelagic state in the 1982 United Nations Convention on the Law of the Sea. Overall, this study concludes that Indonesia plays a role as a driving force for regional cooperation that contributes to the realization of a peaceful, stable, and prosperous ASEAN region.